Influence of irradiation by a particle beam on optical properties of metal mirrors - Poperenko, L.V.; Vinnichenko, M.V.; Kosel, P.B.; Vinnichenko, K.L. (Functional Materials, 2005)
The surface of copper and stainless steel mirrors near the area destroyed by electron beam has been characterized by means of ellipsometric diagnostics. The treatment did not result in any changes in the surface microrelief, independent on the treatment duration, although changes in the ellipsometric parameters have been observed. According to the XPS data, these changes are due to disordering in the about 2 nm thick surface layer resulting from Ar ion implantation. По результатам эллипсометрической диагностики охарактеризована поверхность зеркал из меди и нержавеющей стали вблизи участка, разрушенного электронным пучком. Обработка не изменяла микрорельеф поверхностей независимо от времени обработки, хотя наблюдались изменения эллипсометрических параметров. По данным РФС, эти изменения обусловлены разупорядочением структуры поверхностного слоя толщиной около 2 нм вследствие имплантации ионов аргона. 3а результатами елiпсометричної дiагностики охарактеризовано поверхню дзеркал з мiдi та нержавiючої сталi поблизу зруйнованої електронним пучком дiлянки. Обробка не змiнювала мiкрорельєф поверхонь незалежно вiд тривалостi обробки, хоча спостерiгалися змiни елiпсометричних параметрiв. Цi змiни, за даними РФС, зумовленi розупорядкуванням структури прошарку завтовшки близько 2 нм внаслiдок iмплантацiї iонiв аргону.